A STUDY OF POSSIBLE REVENUE SHARING ON VALUE ADDED TAX - Machfud Sidik (LPPM-STPI, 2020)
This study focuses on the possible application of Value Added Tax (PPN) revenue sharing, including its implications for the financial relationship between the Central and Regional Governments and the possible impact on the DAU allocation. This study also provides strategic advice on approaches to implementing potential VAT reforms and the types of consumption taxes that fall under the authority of local governments. The success of developing fiscal relations between levels of government depends on the right policy environment, especially on effective policies regarding the collection of sources of state/regional revenue. This study provides a comprehensive understanding of the nature of the fiscal relationship between levels of government in terms of efforts to increase tax revenues, both by the Central Government and Regional Governments and explores the sharing of VAT revenues to increase additional sources of funds for the Provincial, Regency and City Governments. VAT revenue sharing is very likely to reduce the vertical imbalance between the Central Government and the Provincial, Regency and City Governments, but on the other hand, this has the potential to increase the horizontal disparity between the Provincial, Regency and City Governments. Thus, PPN reform including profit sharing, in any form requires policy improvement, including in the formulation of DAU reformulation. The implementation of VAT revenue sharing will also increase additional sources of funds for Provincial, Regency and City Governments, including by encouraging collaboration between Central and Regional tax officials, as well as increasing transparency and accountability.